Analysis of Early Childhood Confidence in Overcoming Fear - Aprilianti, Eka (CV. Creative Tugu Pena, 2023)
One of the factors that can affect a child's self-confidence is overcoming fear. Fear is an emotional response to a threat or danger whose source is usually external and consciously faced. The purpose of this study is to find out how self-confidence of young children overcomes fear. This study uses phenomenological qualitative techniques. Notes obtained from informants, five were obtained using the purposive aspect with the criteria of early childhood being able to overcome fears such as not daring to point a finger to answer the teacher's question even though he knew the answer at TKIT Al-Baihaqi. Gather information using semi-structured interviews. The test uses fact analysis with descriptive narrative analysis. The results obtained from this test are that the subject generally feels insecure at school. However, there are subjects who express self-confidence, both as evidenced by being confident in their abilities, easily expressing emotions, being responsible, grateful and optimistic even though they are not perfect. Keywords: self confidence, Overcoming Fear , early childhood